Leukemia inhibitory factor-receptor signalling negatively regulates gonadotrophin-stimulated testosterone production in mouse Leydig Cells. (15th March 2022) - Curley, Michael; Darbey, Annalucia; O'Donnell, Liza; Kilcoyne, Karen R.; Wilson, Kirsten; Mungall, Will; Rebourcet, Diane; Guo, Jingtao; Mitchell, Rod T.; Smith, Lee B.
Abstract: Testicular Leydig cells (LCs) are the principal source of circulating testosterone in males. LC steroidogenesis maintains sexual function, fertility and general health, and is influenced by various paracrine factors. The leukemia inhibitory factor receptor (LIFR) is expressed in the testis and activated by different ligands, including leukemia inhibitory factor (LIF), produced by peritubular myoid cells. LIF can modulate LC testosterone production in vitro under certain circumstances, but the role of consolidated signalling through LIFR in adult LC function in vivo has not been established. We used a conditional Lifr allele in combination with adenoviral vectors expressing Cre-recombinase to generate an acute model of LC Lifr- KO in the adult mouse testis, and showed that LC Lifr is not required for short term LC survival or basal steroidogenesis. However, LIFR-signalling negatively regulates steroidogenic enzyme expression and maximal gonadotrophin-stimulated testosterone biosynthesis, expanding our understanding of the intricate regulation of LC steroidogenic function. Highlights: The leukemia inhibitory factor receptor gene ( Lifr ) was acutely ablated from Leydig cells in adult mouse testes. Wildtype mouse Leydig cells highly express genes required for LIFR signalling that can be activated via multiple ligands. LIFR signalling is not required for short term Leydig cell survival or basal steroidogenesis in the adult testis. LIFR signalling negatively regulates steroidogenic gene expression and gonadotrophin-stimulated testosterone synthesis.